2021
DOI: 10.48550/arxiv.2101.01991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observing gravitational wave polarizations with LISA-TAIJI network

Gang Wang,
Wen-Biao Han

Abstract: Two polarization modes of gravitational wave are derived from the general relativity which are plus and cross modes. However, the alternative theories of gravity can yield the gravitational wave with up to six polarizations. Searching for the polarizations beyond plus and cross is an important test of general relativity. In principle, one space-borne detector, like LISA, could measure the gravitational wave polarizations from a long time observation with its orbital motion. With the comparable sensitivities, t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…LISA's orbit is proposed to be at the ecliptic plane behind the Earth with 20 • trailing angle, and Taiji is planed to be localized in front of the Earth with 20 • leading angle, so that LISA and Taiji could form a space-based network aimed at detecting GW signals within mHz range (i.e. 10 −4 Hz to 1 Hz) [92][93][94][95][96][97][98].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LISA's orbit is proposed to be at the ecliptic plane behind the Earth with 20 • trailing angle, and Taiji is planed to be localized in front of the Earth with 20 • leading angle, so that LISA and Taiji could form a space-based network aimed at detecting GW signals within mHz range (i.e. 10 −4 Hz to 1 Hz) [92][93][94][95][96][97][98].…”
Section: Introductionmentioning
confidence: 99%
“…Orlando et al [97] proposed that the chirality of an isotropic SGWB can be detected by cross-correlating the data streams of the LISA and Taiji. Wang and Han [98] showed that the LISA-Taiji network could improve the observations on the anomalous polarization predicted by the theories beyond general relativity.…”
Section: Introductionmentioning
confidence: 99%